The genus Ctenosciara Tuomikoski (Diptera, Sciaridae) in New Caledonia, with the description of eight new species - Vilkamaa, Pekka; Hippa, Heikki; Mohrig, Werner (Zootaxa, 2012)
The genus Ctenosciara Tuomikoski, 1960, includes the following species in New Caledonia, all newly described: Cteno-sciara cracens sp. n., C. crinita sp. n., C. depilis sp. n., C. depressa sp. n., C. exilis sp. n., C. inflata sp. n., C. lobigerasp. n. and C. obesa sp. n. Some of the species show for the genus previously unknown characters. A key to the New Caledonian species of Ctenosciara is provided.